Estrutura populacional, táticas reprodutivas e alocação de energia em peixes de igarapé da Reserva Ducke, Amazônia Central brasileira - Wolf, Daniela de Fex (Instituto Nacional de Pesquisas da Amazônia - INPA, 2014)
The reproductive cycle of freshwater tropical fish respond to changes in flood pulse, but little is known about the reproductive patterns of fish species in streams that undergo drastic changes depending on local rainfall. This study considered life strategy and patterns of energy allocation in six small fish species from small streams of Reserva Adolpho Ducke, Central Amazonia. Samplings were carried out monthly from January to December/2013, using small seine nets, dip nets and small gill nets. Size structure, length-weight relationship, sex ratio, gonadossomatic index, cavity fat index, body condition, breeding season and its relation to rainfall levels and caloric density in muscle were considered for each species, which were associated with life-histoty strategies of each species. The results showed that Rivulus micropus, Pyrrhulina cf. brevis and Hyphessobrycon aff. melazonatus fit into opportunistic strategy but the viii first two uses energy from the muscle to the development of the gonads and the third one uses energy from other sources; Aequidens pallidus and Crenuchus spilurus are prone to equilibrium strategy and do not use energy from muscle to gonad maturation; Bryconops giacopinii is a seasonal species that does not use muscle energy for gonadal development. Our results indicate that some tactics hypothetically associated with different reproductive strategies may not necessarily be fixed and interdependent, but rather, can be combined in different ways in response to the characteristics and dynamics of the environment where they live.
Keywords: Ecologia Energética; Peixe; Reserva Ducke